2014
DOI: 10.1016/j.eplepsyres.2013.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Early susceptibility for epileptiform activity in malformed cortex

Abstract: Despite early disruption of developmental processes, hyperexcitability is often delayed after the induction of cortical malformations. In the freeze-lesion model of microgyria, interictal activity cannot be evoked in vitro until postnatal day (P)12, despite the increased excitatory afferent input to the epileptogenic region by P10. In order to determine the most critical time period for assessment of epileptogenic mechanisms, here we have used low-Mg2+ aCSF as a second hit after the neonatal freeze lesion to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…This could be due to an increase in distal surface transporter density, to more directly couple with synapses in the hyperexcitable cortex. Previous studies have demonstrated an increase in mEPSPs in the paramicrogyral zone following FL (Jacobs and Prince, 2005 ; Bell and Jacobs, 2014 ), suggesting there may be an increased demand for glutamate uptake.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This could be due to an increase in distal surface transporter density, to more directly couple with synapses in the hyperexcitable cortex. Previous studies have demonstrated an increase in mEPSPs in the paramicrogyral zone following FL (Jacobs and Prince, 2005 ; Bell and Jacobs, 2014 ), suggesting there may be an increased demand for glutamate uptake.…”
Section: Discussionmentioning
confidence: 87%
“…In the FL model, acute cortical brain slices generate epileptiform activity after P12–14 (Jacobs et al, 1996 , 1999 ; Bell and Jacobs, 2014 ). This phenotype is mainatined in the mouse FL model (Figure 1B ) (Andresen et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,24 There are animal models to estimate the risk of epilepsy in a malformed cortex. 25 Even in children who were not born with microcephaly, neuroimaging changes can be severe and cause a substantial risk of epilepsy. 18…”
Section: Epilepsy As Results Of Severe Brain Malformation In Czsmentioning
confidence: 99%
“…One of the reasons for drug‐resistant epilepsy is the nature of the CNS that occurs in this syndrome. The severe pattern of brain abnormalities is a determinant for the occurrence of cortical epileptogenicity with abnormal EEG findings 29 . Most patients with continuous ED were drug‐resistant (72.7%) and were under polytherapy (86.4%), whereas in the others, 45.2% were drug‐resistant and 51.6% were under polytherapy.…”
Section: Discussionmentioning
confidence: 99%